Вплив неоднорідності на процеси трансформації і випромінювання в турбулентній плазмі з верхньогібридною накачкою - Panchenko, V. G.; Porytsky, P. V. (Publishing house "Academperiodika", 2019)
On the basis of the kinetic theory of fluctuations, the processes of the longitudinal Langmuir wave transformation into a transverse electromagnetic wave in the turbulent inhomogeneous plasma have been studied. The plasma turbulence is assumed to arise owing to the parametric decay of the upper hybrid pump wave into a daughter wave and electron-drift oscillations. The transformation coefficient under the parametric instability saturation conditions is determined. The intensity of the electromagnetic radiation emission from the plasma is calculated, and its dependence on the plasma and pump wave parameters is found.